Invasive Fishes Interact With Temperature to Reshape Community Size Structure Across Climatic Zones - Barbbara Silva Rocha; Ignasi Arranz; Henrique C. Giacomini; Daniel M. Perkins; Gilberto Nepomuceno Salvador; José Luís Costa Novaes; Jorge Iván Sánchez‐Botero; Angelo Antonio Agostinho; Paulo Santos Pompeu; Rosemberg Fernandes Menezes; Silvia Yasmin Lustosa‐Costa; Telton Pedro A. Ramos; et al. (Global Change Biology, 2026)
The body size spectrum (or individual size distribution) is a simple yet widely recognized approach that links individual and population traits to community structure and ecosystem functions, making it a valuable indicator of anthropogenic effects. However, the assessment of size spectra in the context of biological invasions remains poorly explored. We investigated the impacts of non‐native (NN) fish invasions on the size structure of 667 lacustrine fish communities across climatic regions (temperate, tropical, and subtropical systems) and the roles of trophic position and temperature in modulating these effects. We found that fish communities under higher invasion pressure exhibit flatter, or less negative, size spectrum exponents. Also, NN species from lower trophic levels can have greater impacts than piscivorous NNs by reshaping size spectra and reducing the overall biomass of native communities. We also observed that piscivore NNs and NNs from lower trophic levels interacted positively with temperature to drive the size spectrum exponent and total biomass of the native communities, respectively. These results can be explained by two main mechanisms: (i) NN piscivores primarily act through size‐selective predation (top–down control), which may be intensified particularly on small prey in warmer lakes, and (ii) NN fish from lower trophic levels primarily act through competition, hence reducing the numerical abundance of small‐sized native fish, which may be more vulnerable in colder and less productive lakes. These mechanisms are leading to flatter size spectrum exponents mainly at higher temperatures and to a decline in the total biomass of the native community, mainly at lower temperatures, effectively reversing the expected temperature–size rule pattern. By disentangling the trophic and temperature‐dependent mechanisms through which NN fishes affect size structure, this study strengthens our ability to anticipate the impact of biological invasions on freshwater communities and their ecosystem functions and services under global change.